DESAIN SARINGAN PASIR LAMBAT - Utomo, Sudiyo; Sir, Tri M. W.; Sonbay, Albert (Jurnal Teknik Sipil, 2012)
Kolhua IPAB is a means of channeling water to the people and surrounding villages Kolhua, however IPAB has a major problem is turbidity. Slow sand filtration (SPL) is a technique used to improve water quality. Runoff and water quality modeling is obtained by making use of PVC pipe 6